A checklist of Burmanniaceae in Eastern Indochina with a new record from Vietnam, Burmannia itoana - Nuraliev, Maxim S.; Yudina, Sophia V.; Truong, Ba Vuong; Dang, van Son; Kopylov-Guskov, Yury O.; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Zhang, Dianxiang (Phytotaxa, 2022)
An updated checklist of the family Burmanniaceae in Cambodia, Laos and Vietnam is provided. The checklist comprises a single genus, Burmannia, and 15 species, of which one is fully autotrophic, six species are partially mycoheterotrophic, and eight species are fully mycoheterotrophic (non-photosynthetic). Burmannia itoana earlier known only from Japan and China is reported from Vietnam for the first time, based on our collections of this species from northern and southern parts of the country. The newly recorded species, as well as a selection of several other Vietnamese species of Burmannia, are illustrated with analytical photographs of floral structure. A key for identification of Burmannia in the countries of Eastern Indochina is presented.